Nutritional value and growth performance of sea worms (Nereis sp.) fed with Hermetia illucens maggot flour and grated coconut (Cocos nucifera) as natural feed - Vivi Endar Herawati; Pinandoyo Pinandoyo; Seto Windarto; Nurmanita Rismaningsih; Putut Har Riyadi; YS Darmanto; Ocky Karna Radjasa (Society for Indonesian Biodiversity, 2020)
Abstract. Herawati VE, Pinandoyo, Windarto S, Rismaningsih N, Riyadi PH, Darmanto YS, Radjasa OK. 2020. Nutritional value and growth performance of sea worms (Nereis sp.) fed with Hermetia illucens maggot flour and grated coconut (Cocos nucifera) as natural feed. Biodiversitas 21: 5431-5437. Sea worms are one of the natural feeds used for shrimp aquaculture. This study aimed to investigate the growth performance and nutritional quality of sea worms (Nereis sp.) fed with Hermetia illucens maggot flour and grated coconut (Cocos nucifera). Nereis sp. individuals were cultured at a density of 100/plastic container for 35 days, and fed twice daily with a feeding rate of 5% of the total body weight. This study used five treatments, i.e.: A. 50% maggot flour and 50% coconut grated, B. 75% maggot flour and 25% coconut grated, C. 25% maggot flour and 75% grated coconut, D. 100% maggot flour, and E. 100% coconut grated. The results showed that the sea worms fed on maggot flour and grated coconut had a significant effect (P < 0.01) on the survival rate (SR), feed conversion rate (FCR), and feed efficiency. Treatment D showed the highest absolute growth value, specific growth rate (SGR), feed efficiency, and SR (0.45 g, 3.25%, 49.23%, and 99.67%). Feeding rate n ranged from 30.50% to 34.67%, and the FCR value ranged from 2.07-2.43%. The highest nutrient contents were observed in treatment D, with 54.05% protein, 22.54% fatty acid, 55.46 ppm methionine, and 10.98% EPA. This result suggested that Nereis sp. fed with 100% maggot flour had the greatest nutritional quality and growth performance.